2023
DOI: 10.3390/pathogens12050698
|View full text |Cite
|
Sign up to set email alerts
|

Key Aspects of Coronavirus Avian Infectious Bronchitis Virus

Abstract: Infectious bronchitis virus (IBV) is an enveloped and positive-sense single-stranded RNA virus. IBV was the first coronavirus to be discovered and predominantly causes respiratory disease in commercial poultry worldwide. This review summarizes several important aspects of IBV, including epidemiology, genetic diversity, antigenic diversity, and multiple system disease caused by IBV as well as vaccination and antiviral strategies. Understanding these areas will provide insight into the mechanism of pathogenicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 112 publications
0
1
0
Order By: Relevance
“…The current classification scheme classifies IBV into seven genotypes (GI-GVII) and a total of 35 distinct lineages [ 8 ]. QX-type (GI-19) strains are the most prevalent in six Asian countries, including Japan, Korea, India, Indonesia, Thailand, and China, and 793B-type (GI-13) strains are the second most prevalent lineage in these countries except Korea [ 21 ]. However, during 2013–2015, 89.8% isolates were the QX-type (GI-19), TW I-type (GI-7), and 4/91-type (GI-13) [ 21 ], with the QX-type (GI-19) as the most common isolates (46.7%) in China [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current classification scheme classifies IBV into seven genotypes (GI-GVII) and a total of 35 distinct lineages [ 8 ]. QX-type (GI-19) strains are the most prevalent in six Asian countries, including Japan, Korea, India, Indonesia, Thailand, and China, and 793B-type (GI-13) strains are the second most prevalent lineage in these countries except Korea [ 21 ]. However, during 2013–2015, 89.8% isolates were the QX-type (GI-19), TW I-type (GI-7), and 4/91-type (GI-13) [ 21 ], with the QX-type (GI-19) as the most common isolates (46.7%) in China [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…QX-type (GI-19) strains are the most prevalent in six Asian countries, including Japan, Korea, India, Indonesia, Thailand, and China, and 793B-type (GI-13) strains are the second most prevalent lineage in these countries except Korea [ 21 ]. However, during 2013–2015, 89.8% isolates were the QX-type (GI-19), TW I-type (GI-7), and 4/91-type (GI-13) [ 21 ], with the QX-type (GI-19) as the most common isolates (46.7%) in China [ 22 ]. In 2016–2018, an epidemiological survey conducted in Henan, Hubei, and Hunan provinces showed that the prevalence of GI-19 (QX) was 48.2% in 56 isolates [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its genomic RNA is translated into fourteen non-structural proteins, four structural proteins, and four accessory proteins [117,118]. Infectious bronchitis, due to the rapid IBV mutations, can now be diagnosed in different avian species beyond chickens, leading to constant-health and economic-risk factors for the poultry industry [119]. As the first known coronavirus and study model for gammacoronaviruses, it is known that IBV can recruit ER stress and the UPR mechanism to promote viral pathogenesis [120].…”
Section: Gammacoronaviruses: the Case Of Infectious Bronchitis Virus ...mentioning
confidence: 99%
“…Infectious bronchitis (IB) is an acute and highly contagious disease caused by the infectious bronchitis virus (IBV), affecting the respiratory, reproductive, nervous, and urinary systems of chickens [ 1 , 2 , 3 ]. In the global poultry industry, IBV is one of the most important viruses that seriously threatens the development of the industry [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%